Using Multi-fluorinated Bile Acids and In Vivo Magnetic Resonance Imaging to Measure Bile Acid Transport - Felton, Jessica (J Vis Exp, 2016)
Along with their traditional role as detergents that facilitate fat absorption, emerging literature indicates that bile acids are potent signaling molecules that affect multiple organs; they modulate gut motility and hormone production, and alter vascular tone, glucose metabolism, lipid metabolism, and energy utilization. Changes in fecal bile acids may alter the gut microbiome and promote colon pathology including cholerrheic diarrhea and colon cancer. Key regulators of fecal bile acid composition are the small intestinal Apical Sodium-dependent Bile Acid Transporter (ASBT) and fibroblast growth factor-19 (FGF19). Reduced expression and function of ASBT decreases intestinal bile acid up-take. Moreover, in vitro data suggest that some FDA-approved drugs inhibit ASBT function. Deficient FGF19 release increases hepatic bile acid synthesis and release into the intestines to levels that overwhelm ASBT. Either ASBT dysfunction or FGF19 deficiency increases fecal bile acids and may cause chronic diarrhea and promote colon neoplasia. Regrettably, tools to measure bile acid malabsorption and the actions of drugs on bile acid transport in vivo are limited. To understand the complex actions of bile acids, techniques are required that permit simultaneous monitoring of bile acids in the gut and metabolic tissues. This led us to conceive an innovative method to measure bile acid transport in live animals using a combination of proton ((1)H) and fluorine ((19)F) magnetic resonance imaging (MRI). Novel tracers for fluorine ((19)F)-based live animal MRI were created and tested, both in vitro and in vivo. Strengths of this approach include the lack of exposure to ionizing radiation and translational potential for clinical research and practice.